Response of systemic hemodynamic parameters to changes in blood viscosity in spontaneously hypertensive rats - A. V. Sidekhmenova; A. M. Anishchenko; O. I. Aliev; O. A. Ulyakhina; O. I. Poleshchuk; M. B. Plotnikov (Бюллетень сибирской медицины, 2025)
Aim. To study the response of systemic hemodynamic parameters to a decrease in blood viscosity in spontaneously hypertensive rats (SHR) compared to normotensive Wistar rats.Materials and methods. Systemic hemodynamic parameters were recorded using the MP150 system (Biopac Systems, Inc., USA). Blood viscosity was measured using a Brookfield DV–II+Pro rotational viscometer (Brookfield Engineering Labs Inc., USA) at 36°C and a shear rate of 450 s–1. Blood viscosity was reduced using isovolemic hemodilution.Results. The decrease in the blood viscosity in Wistar rats was not accompanied by significant changes in the parameters of systemic hemodynamics. Only a slight decrease in the mean blood pressire was revealed, probably associated with the experimental conditions and the effect of isoflurane anesthesia. Unlike normotensive animals, in SHR isovolemic hemodilution led to a marked decrease in total peripheral vascular resistance, heart rate, blood pressure, and an increase in stroke volume. At the same time, in SHR rats, the hypotensive reaction of blood pressure in response to a decrease in blood viscosity was 3 times greater than in Wistar rats, which indicates impaired vascular tone regulation in response to a change in shear stress.Conclusion. Thus, in normotensive animals, a decrease in blood viscosity as a result of isovolemic hemodilution does not cause changes in the main parameters of systemic hemodynamics. In contrast, in spontaneously hypertensive animals, total peripheral vascular resistance and blood pressure decrease alongside with blood viscosity, indicating impaired endothelium-dependent vascular tone regulation in response to changes in shear stress. The results obtained substantiate the use of drugs that reduce blood viscosity as a promising direction in the complex pharmacotherapy of hypertension and its complications.